A Cardioprotective Role of Nerium oleander with the Expression of Hypoxia Inducible Factor 2A mRNA by Increasing Antioxidant Enzymes in Rat Heart Tissue - Hitit, Mustafa; Corum, Orhan; Corum, Duygu Durna; Donmez, Huseyin; Cetin, Gul; Dik, Burak; Er, Ayse (Universidade Federal do Rio Grande do Sul, 2018)
Background: Nerium oleander (NO) distillate is used to either protect heart cells against oxidative stress or reduce the risk of cardiovascular disease by regulating the production of reactive oxygen species. Hypoxia-inducible factors (HIFs) regulate cellular antioxidant defense mechanisms under hypoxic conditions in which heart cells survive; however, the key responsible mechanism of NO distillate for cardioprotection remains elusive. The objective of this study was to evaluate the effects on heart tissue at different time intervals after administering NO distillateintraperitoneally (IP) while considering the transcriptional regulation of HIFs and representative antioxidant enzymes.Materials, Methods & Results: The NO plant was chopped, and distillated water was added. The mixture was distilled, and the distillate separated and collected into tubes, after which it was lyophilized to obtain dry material. Twenty male Wistar albino rats (2-3 month-old, 250-300 geach) were used in the study. The rats were randomly divided into four groups. The control group (n = 5) received IP injections of saline; the remaining 15 rats received IP injections of a single dose of 7.5 mL NO distillate. The NO distillate injected rats were divided into three groupsaccording to the time from injection to harvest the heart tissue samples. The tissues were collected at 0 h (control; n = 5), 2 h (group 2; n = 5), 4 h (group 3; n = 5), and 8 h (group 4; n = 5) after injection and under general anesthesia (60 mg/kg ketamine, IP + 10 mg/kg xylazine, IP).Quantitative polymerase chain reaction (qPCR) was used to assess the expression profiles of the genes of interest in the heart tissues. Hypoxanthine phosphoribosyltransferase was used as the reference gene. The expression of manganese superoxide dismutase (MnSOD) mRNA was in a steady state level between the control group and group 2 (P > 0.05); however, it significantly increased in group 3 and 4 compared with that in the control (P < 0.05). Expression of catalase (CAT) mRNA was significantly higher in group 2 than in the control group (P < 0.05) although it was lower in group 3 and 4 than in group 2 (P < 0.05); however, it appeared to be similar among the control group, group 3, and group 4 (P > 0.05). Copper (Cu) SOD mRNA was equallyexpressed in both the control group and group 2 (P > 0.05) but was lower in group 3 and 4 than in group 2 (P < 0.05). Expressions of HIF1A, HIF2A, and HIF3A mRNA were detected in the rat heart tissues in the control and 2, 4, and 8 h after administration of NO distillate. Expression ofHIF1A mRNA was in a steady state and did not differ among groups 2, 3, and 4 (P > 0.05). Similarly, the expression of HIF2A mRNA did not change between the control group and group 2 (P > 0.05); however, it was higher in group 3 than in the control (P < 0.05) and tended to behigher in group 3 than in group 2 (P = 0.063). HIF3A mRNA expression did not change significantly in the heart tissue of any of the groups (P > 0.05).Discussion: The present study using rats determined that MnSOD, CAT, CuSOD, HIF1A, HIF2A, and HIF3A mRNA are expressed in the heart tissues after administration of NO distillate. The increased expression of HIF2A mRNA after 4 h in accordance with a rise in CAT mRNA after 2 h, and MnSOD mRNA after 4 and 8 h might confirm the role of HIF2A mRNA in oxidative stress defense by regulating antioxidant enzymes; consequently, this study may expand our understanding of uses of NO distillate with respect to molecular pathways.
Keywords: hypoxia inducible factors; antioxidant enzymes; cardioprotection; gene expression; Nerium oleander; 3. Good health